TOP: prospective evaluation of a volume based, computer assisted method for transperineal optimized prostate biopsy - Kesch, Claudia; Radtke, Jan Philipp; Gasch, Claudia; Dieffenbacher, Svenja; Klein, Tilman; Schlemmer, Heinz-Peter; Wieczorek, Kathrin; Hohenfellner, Markus; Hadaschik, Boris (Urologia internationalis, 2017)
Objective: This study is a prospective evaluation of a volume-based, computer-assisted method for transperineal optimized prostate (TOP) biopsy. The TOP algorithm automates core planning for systematic prostate biopsies using the 3-dimensional organ contour and an alterable volume for tumors to be excluded. Subjects and Methods: MRI-transrectal ultrasound fusion biopsy with MRI-targeted biopsies (TBs) and systematic-TOP biopsies were performed on 172 men between October 2013 and March 2014. Systematic biopsies were placed according to TOP for detection of tumor volumes >0.5 mL with a minimum of 80% organ coverage in prostates up to 50 mL (70% in larger organs). Results: Median 24 TOP cores and 3 MRI-TBs have been placed. Prostate cancer (PCa) was detected in 112 of 172 (65%) of men; TOP detected 109 (97%) and TB 62 (55%). Significant cancer (Gleason score ≥7) was detected in 75 (44%) of men and of these TOP detected 73 of 75 (97%) and TB 51 of 75 (68%). Overall, systematic-TOP sampling significantly outperformed TB for the detection of both, all PCa as well as significant PCa (p < 0.0001, p = 0.0005). Conclusion: The TOP method is innovative by integrating the individual prostate volume and PCa volume detection thresholds. In the present cohort, it diagnosed more significant tumors than TB alone. However, at the same time, more low-risk tumors are detected.